(untitled) (Research, Society and Development, 2024)
This study aimed to understand the knowledge of the Puyanawa, an indigenous people inhabiting the Upper Juruá River Valley, Acre, regarding the agrobiodiversity of food plants, their management, conservation, and use, with the purpose of contributing to the expression and cultural strengthening, highlighting the importance of the territory for the well-being of forest peoples. The qualitative study was conducted through semi-structured interviews, guided tours/Walk-in-the-woods, and food recalls, 33 families, comprising 81 individuals, were interviewed. Ninety-five species of food plants were found in the agroecosystems used by the Puyanawa, representing an interesting diversity of sources of vitamins, proteins, and minerals. The production of food species provides a regular supply throughout the year, with seasonality being one of the factors ensuring this diversification. The plants found in agroecosystems significantly contribute to family nutrition, and the vegetables that make up the basis of the diet are predominantly of domestic origin. On the other hand, we can observe a strong tendency for globalized foods to gain space in daily diets, potentially compromising health and threatening the food and nutritional security and sovereignty of the Puyanawa. We believe that the attitude of indigenous peoples in ensuring the resilience and conservation of their agricultural practices has much to contribute to all of humanity. We emphasize the invaluable value of agroecosystems and traditional knowledge associated with food plants for the autonomy and well-being of forest peoples.